EVALUASI KETERSEDIAAN OBAT ESENSIAL UNTUK ANAK DI INSTALASI FARMASI DINAS KESEHATAN KABUPATEN/KOTA DAERAH ISTIMEWA YOGYAKARTA - , Eugenia Vivi Mayang Sari ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background. One of World Health Organization (WHO) programs in reducing child mortality is Make Medicines Child Size. The aim is to ensure children receive appropriate medicines and the ultimate goal is medicines are available for children in appropriate dosage forms. The Indonesian Government has conducted various effort to achieve the goals. One of them is enclosing pediatric formulas to the National Essential Medicine List 2011. Methods. This was a descriptive analytical study with prospective data collections. Information on availability and factors influencing the availability are collected by means of observation and in-depth interviews Results. The results show that the availability of essential medicines with pediatric formulas ranges between 49%-56%, i.e., Bantul 54%, Gunungkidul 49%, Kulonprogo 56%, Sleman 51%, and Yogyakarta 49%. Although there are selection process, procurement, and stock management which look into the availability of pediatric formulation, it is revealed that there is no regency /municipality policy and budget allocation to supporting such concern. Conclusion. The availability formulation of essential medicines for children is low, i.e.,56% at all Regency/Municipality. Factors influencing the availability vary among Regency/Municipality, including inadequate policy, financing, drug selection, drug procurement and stock management, drug usage, product quality, administration management, monitoring and management information system. The first two factors are the most prominent in all Regency/Municipality.